EVALUASI KELENGKAPAN ADMINISTRATIF RESEP DARI DOKTER SPESIALIS ANAK PADA TIGA APOTEK DI KOTA MANADO - Mamarimbing, Marina; Fatimawali, Fatimawali; Bodhi, Widdhi (PHARMACON, 2012)
Prescription can reduce the administrative / prevent dangerous medication errors, withadverse effects on patients by the drugs used during the management of health care. This studyis aimed to evaluate the administrative prescriptions by examining the possibility of medicationerrors by a Pediatricians at three pharmacies in the city of Manado. This is a descriptive studyconducted a retrospective review of patient prescriptions. The method of sampling took randomreceipts using the Slovin formula. 12,225 receipts was vised in the three pharmacy and found338 sheets sample of prescription from period of January to December 2011 then processed andevaluated administrative completeness. Administrative completeness prescription written by apediatrician at the Manado City Permit Practice (11.37%), Address patients (53.7%), Gender(0%), weight loss (27.5%), Age (78 , 3%), date prescription (98.4%) and to mark the R /, DoctorName, Address Doctor, Initials Doctor, Patient Name, Drug Name, Dosage, Number of Drugs,How to use a clear (100%). From these data we can conclude the potential occurrence ofmedication errors and can not find any recipes that meet the screening criteria for theprescription paperwork based on the Decree of the Minister of Healthno.:1027/MENKES/SK/1X/2004.Keywords: Administrative Complete Receipts, Receipts Pediatrician, Medication Error